Analysis of students' conceptions of vertebrate diversity using concept maps - Topik Hidayat; Yayan Sanjaya; Rifki Risma Munandar (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The concept of the characteristics of biodiversity is vital to be understood by students as a first step in managing and preserving the biodiversity. This study aimed to describe students' conceptions in vertebrate diversity and classification courses using concept maps. This research was conducted at one of the Biology Education Study Program Universities in Bogor, carried out in the even semester of 2023/2024, involving 42 participants. Data were collected through observation techniques with concept maps. The analysis process consisted of collecting information, simplifying information, presenting information, and drawing conclusions. The analysis results illustrate that students' conceptions of classification systematics, variability, phylogenetics, and preserving diversity and the environment show that they know the concept by 40.83%. The concept of the role of diversity in human life experienced the highest conception understanding of 54.61%. Students experienced many misconceptions about the concepts of characteristics, anatomy and morphology, genomes, and variability of biodiversity by 36.16%. Then 52.77% of students not knowing the concept of preserving diversity and the environment. The results of the concept map illustrate that most students still experience misconceptions and not knowing the concept of vertebrate diversity in detail. Therefore, training and strengthening concepts for students in classifying vertebrate animals are needed.Abstrak. Konsep mengenai karakteristik makhluk hidup penting untuk dipahami oleh mahasiswa sebagai langkah awal dalam mengelola dan melestarikan keanekaragaman makhluk hidup. Tujuan penelitian ini untuk mendeskripsikan konsepsi mahasiswa pada mata kuliah keanekaragaman dan klasifikasi vertebrata menggunakan peta konsep. Penelitian ini dilakukan di salah satu Perguruan Tinggi Prodi Pendidikan Biologi di Bogor, dilaksanakan pada semester genap tahun 2023/2024 dengan melibatkan 42 orang partisipan. Data dikumpulkan melalui teknik observasi dengan peta konsep. Proses analisis terdiri dari pengumpulan informasi, penyederhanaan informasi, penyajian informasi, dan penarikan kesimpulan. Hasil analisis menggambarkan bahwa konsepsi mahasiswa tentang sistematika klasifikasi, variabilitas, filogenetik dan konsep pelestarian keanekaragaman makhluk hidup dan lingkungan menunjukkan tahu konsep sebesar 40,83%. Konsep mengenai peranan keanekaragaman makhluk hidup bagi kehidupan manusia mengalami pemahaman konsepsi paling tinggi sebesar 54.61%. Mahasiswa banyak mengalami miskonsepsi pada konsep karakteristik, anatomi dan morfologi, genom, dan variabilitas makhluk hidup sebesar 36.16%. Kemudian 52.77% mahasiswa tidak tahu konsep pelestarian keanekaragaman makhluk hidup dan lingkungan. Hasil peta konsep menggambarkanan bahwa sebagian besar mahasiswa masih mengalami miskonsepsi dan tidak tahu konsep mengenai konsep keanekaragaman vertebrata secara detail. Oleh karenanya diperlukan latihan dan penguatan konsep bagi mahasiswa dalam klasifikasi hewan vertebrata.